The Relevance of Sufi Values in Maintaining Mental Health in Modern Society - Durrotul Masruroh; Fatima Al-Hammadi (Aafiyah: Jurnal Multidisiplin Ilmu, 2026)
Mental health has become one of the most critical issues in modern society due to increasing psychological pressures, social competition, technological dependency, and weakening spiritual awareness. This study aims to examine the relevance of Sufi values in maintaining mental health within contemporary social life. The research employs a qualitative approach through literature review and contextual analysis of Sufi teachings related to emotional well-being, spiritual resilience, and psychological balance. Data were collected from classical Islamic literature, contemporary psychological studies, and scholarly discussions concerning spirituality and mental health. The findings indicate that Sufi values such as dhikr (remembrance of God), tawakkul (trust in God), sabr (patience), zuhud (moderation toward worldly attachment), and tazkiyat al-nafs (self-purification) significantly contribute to emotional stability, stress reduction, and psychological resilience. These spiritual practices help individuals manage anxiety, strengthen self-awareness, develop meaningful life perspectives, and maintain positive social relationships. The study also reveals that Sufi teachings provide holistic approaches integrating spiritual, emotional, cognitive, and social dimensions of human well-being. In addition, collective spiritual practices within Sufi communities contribute to social support and emotional connectedness, which are important factors in mental health maintenance. Despite modern misconceptions that Sufism is outdated or detached from contemporary realities, the findings demonstrate that Sufi values remain highly relevant for addressing existential crises and psychological challenges in modern society. Therefore, integrating Sufi principles into educational, social, and mental health frameworks may offer valuable strategies for promoting emotional balance and spiritual well-being in contemporary life.